Gender and sexuality in formation of teacher: a mapping of research between North and Northeast - Cardoso, Lívia de Rezende; Bertoldo, Tássia Alexandre Teixeira; Santos, Linda Brasil de Azevedo (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This article builds a mapping with the objective of analyzing theses and dissertations in gender, sexuality and teacher education defended in postgraduate programs in higher education institutions in the North and Northeast regions of Brazil. For that, theses and dissertations were mapped from 2006 to 2018 through a state-of-the-art type study. For this article, we bring the 22 works that involve teacher formation and, considering the objective of this study, we organized the discussion in two units of meaning: the first focused on the works that analyzes the conception of teachers in initial formation and the second, the works focused on the curriculum of this formation. In this perspective, some contributions, limits and possibilities of this academic production were observed.